Chap3_Sec6

# Chap3_Sec6 - f x = l n x then f ’ x = 1 x Thus f ’(1 =...

This preview shows pages 1–8. Sign up to view the full content.

1 (log ) ln a d x dx x a = DERIVATIVES OF LOG FUNCTIONS (Section 3.6) Prove s Let y = log a x. Then, a y = x . s Differentiating this equation implicitly with respect to x , we get: s So, (ln ) 1 y dy a a dx = 1 1 ln ln y dy dx a a x a = =

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Differentiate y = l n( x 3 + 1). s To use the Chain Rule, we let u = x 3 + 1. s Then y = l n u . Find DERIVATIVES OF LOG FUNCTIONS (Section 3.6) Example 1 Example 2 ln(sin ) d x dx
Differentiate Differentiate f ( x ) = log 10 (2 + sin x ). ( ) ln f x x = DERIVATIVES OF LOG FUNCTIONS (Section 3.6) Example 3 Example 4

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
1 st way : Find 2 nd way : Simplify the given function using the laws of logarithms, then differentiate: 1 ln 2 d x dx x + - DERIVATIVES OF LOG FUNCTIONS Example 5 (3.6)
Find f ’ ( x ) if f ( x ) = l n | x |. s Since s Differentiate ln if 0 ( ) ln( ) if 0 x x f x x x > = - < DERIVATIVES OF LOG FUNCTIONS (Section 3.6) Example 7 3 / 4 2 5 1 (3 2) x x y x + = + Example 6

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
Differentiate . s 1 st way : Use logarithmic differentiation, we have: s 2 nd way : Write LOGARITHMIC DIFFERENTIATION Example 8 (3.6) x y x = ln ( ) x x x x e =
We have shown that, if

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: f ( x ) = l n x , then f ’ ( x ) = 1/ x . Thus, f ’ (1) = 1 . Now, we use this fact to express the number e as a limit. From the definition of a derivative as a limit, we have: THE NUMBER e AS A LIMIT (Section 3.6) 1 (1 ) (1) (1 ) (1) '(1) lim lim ln(1 ) ln1 1 lim lim ln(1 ) lim ln(1 ) h x x x x x f h f f x f f h x x x x x x → → → → → +-+-= = +-= = + = + As f ’ (1) = 1 , we have If we put n = 1/ x , then n → ∞ as x → + . So, an alternative expression for e is: 1 lim ln(1 ) 1 x x x → + = 1/ 1 lim ln(1 ) 1 ln(1 ) 1 lim lim(1 ) x x x x x x x x e e e e x → + + → → = = = = + THE NUMBER e AS A LIMIT (Section 3.6) 1 lim(1 ) x x e x → = + 1 lim 1 n n e n →∞ = +...
View Full Document

## This note was uploaded on 05/23/2011 for the course MAC 2311 taught by Professor Noohi during the Fall '08 term at FSU.

### Page1 / 8

Chap3_Sec6 - f x = l n x then f ’ x = 1 x Thus f ’(1 =...

This preview shows document pages 1 - 8. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online